Efektivitas Kebijakan Digitalisasi Pajak Bea Perolehan Hak Atas Tanah dan Bangunan di Provinsi Daerah Khusus Jakarta - Rosadi, Andi Ahmad Marsulin; Inayati, Inayati (Syntax Literate, 2025)
This study aims to analyze the effectiveness of the digitalization policy of the Land and Building Acquisition Duty (BPHTB) in the Special Capital Region of Jakarta in promoting transparent, efficient, and accountable local tax governance. The research employs a descriptive qualitative approach, collecting data through interviews, observations, and document analysis involving the Regional Revenue Agency (Bapenda), Land Deed Officials (PPAT), and taxpayers using the e-BPHTB system. The findings indicate that the digital tax system has improved administrative efficiency and service transparency. However, its overall effectiveness remains limited due to technological infrastructure issues, uneven human resource capacity, weak inter-agency coordination, and low digital literacy among taxpayers. From the perspective of good governance, the e-BPHTB system fulfills the principles of transparency and accountability, but responsiveness and public participation require further enhancement. The study recommends strengthening system integration across institutions, providing digital training for tax officers and PPAT, improving taxpayers’ digital literacy, and establishing a regular policy evaluation mechanism to ensure the sustainability of digital tax governance effectiveness.